2003
DOI: 10.1002/dvdy.10281
|View full text |Cite
|
Sign up to set email alerts
|

Loss of maternal Smad5 in zebrafish embryos affects patterning and morphogenesis of optic primordia

Abstract: The mechanisms of patterning and morphogenesis of vertebrate eye primordia are heavily debated. Taking advantage of the maternal effect of a zebrafish smad5 null mutation (Mm169), we investigate the effect of early signaling by members of the bone morphogenetic proteins (Bmps) on eye field patterning and optic vesicle morphogenesis. In contrast to previous Xenopus and chick studies demonstrating a late dorsalizing effect of Bmp4 expressed in the dorsal neural retina itself, we show that patterning of the eye p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…According to the available data obtained on nematodes, insects, and mice, so called maternal effect genes encoding maternal mRNA control not only the earliest developmental stages but can affect the formation of embryo and its morphology at the late stages (Johnston and Nusslein-Volhard, 1992;Reinhold, 2002;Gilbert, 2003). Similar results were also obtained on fishes (Odenthal et al, 1996;Bauer et al, 2001;Hammerschmidt et al, 2003;Kishimoto et al, 2004).…”
Section: Combinations Of Speciessupporting
confidence: 80%
“…According to the available data obtained on nematodes, insects, and mice, so called maternal effect genes encoding maternal mRNA control not only the earliest developmental stages but can affect the formation of embryo and its morphology at the late stages (Johnston and Nusslein-Volhard, 1992;Reinhold, 2002;Gilbert, 2003). Similar results were also obtained on fishes (Odenthal et al, 1996;Bauer et al, 2001;Hammerschmidt et al, 2003;Kishimoto et al, 2004).…”
Section: Combinations Of Speciessupporting
confidence: 80%
“…BMPs have multiple functions during early and late stages of vertebrate eye development (Koshiba-Takeuchi et al, 2000;Sakuta et al, 2001;Adler and Belecky-Adams, 2002;Sasagawa et al, 2002;Hammerschmidt et al, 2003;Murali et al, 2005). For example, deletion of the BMPR1A/B function specifically within the mouse retina leads to reduced growth of the NR and failure of retinal neurogenesis (Murali et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…BMPs are involved in several aspects of vertebrate eye development. For example, BMP signalling is required for patterning the eye primordia during blastula and gastrula stages in zebrafish (Hammerschmidt et al, 2003), whereas later on BMPs function in both dorsal and ventral patterning of the vertebrate eye (Koshiba-Takeuchi et al, 2000;Sakuta et al, 2001;Adler and Belecky-Adams, 2002;Sasagawa et al, 2002;Murali et al, 2005). In addition, the generation of retinaspecific BMP type 1 receptor mutant mice has shown that different threshold levels of BMP signalling regulate distinct developmental processes such as dorsoventral patterning of the NR, as well as NR growth and differentiation (Murali et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Failure to suppress Wnt/ßcatenin signaling leads to a fate conversion of both the eye field and prospective telencephalon to a caudal diencephalic identity (Heisenberg et al, 2001; Houart et al, 2002) (Kim et al, 2000). Similarly, levels of Bmp activity are low within eye field and suppression of Bmp signaling in the anterior neural plate and bordering ectodermal cells can lead to expansion of the eye field (Houart et al, 2002; Hammerschmidt et al, 2003; Gestri et al, 2005) FGF, IGF and non-canonical Wnt pathways most likely promote eye field formation indirectly through antagonism of Wnt/ßcatenin signaling (Richard-Parpaillon et al, 2002; Kudoh et al, 2004; Cavodeassi et al, 2005). Surprisingly, purinergic signaling also promotes eye formation although the mechanisms of action are not known (Masse et al, 2007).…”
Section: Ocular Disease Modelsmentioning
confidence: 99%